Conformation and Configuration of Tertiary Amines via GIAO-Derived 13C NMR Chemical Shifts and a Multiple Independent Variable Regression Analysis - Sebag, Albert B; Forsyth, David A; Plante, Marc A (Journal of organic chemistry, 2001)
The 13C chemical shifts of six tertiary amines of unambiguous conformational structure are compared to predicted 13C NMR chemical shifts obtained via empirically scaled GIAO shieldings for geometries from MM3 molecular mechanics calculations. An average deviation, |Δδ|av, of 0.8 ppm and a maximum deviation, |Δδ|max, of 2.8 ppm between predicted and experimental 13C shifts of the six tertiary amines of unambiguous structure are found. In several cases of tertiary amines subject to rapid exchange, where experimental 13C shifts at room temperature are weighted averages of multiple conformers, a comparison of calculated 13C shifts of all reasonable MM3 predicted conformers with experimental 13C shifts via a multiple independent variable regression analysis provides an efficient method of determining the major and minor conformers. The examples presented are 2-methyl-2-azabicyclo[2.2.1]heptane and 1,6-diazabicyclo[4.3.1]decane, which each have two expected contributing structures, and 2-(diethylamino)propane and 1,8-diazabicyclo[6.3.1]dodecane, where ten and seven low-energy conformers, respectively, are predicted by MM3 calculations.